(untitled) (American Journal of Social Development and Entrepreneurship, 2024)
The study aims to determine the viability of the proposed program Bachelor of Science in Public Management (BSPM) and examine it by using SWOT analysis (strength, weakness, opportunities, and threats) internally and externally enabling us to see the big picture and whether the proposed curriculum program is feasible to be implemented in the Samar State University (SSU) complete facilities, and available faculty to manage the program administratively and academically. The study involved senior high school students with a sample size of 724 student respondents. This study employed a descriptive method by facilitating a survey questionnaire issued to respondents and analyzing their preferences. Descriptive viability data were also obtained by extracting information from the Human Resource Officers like recommendations for enrolment and hiring assurances for upcoming enrollees and future graduates. The results of the feasibility were ground-breaking because of the high number of students who want to enroll for the BSPM about 368 or 50.83%, if offered in SSU and their top reasons are the University offers free tuition, scholarships, and grants 173 (23.90%), student says it’s aligned in their Senior high school strand with several answers 138 (19.6%) and a tie in 3rd rank, the SSU offers quality education with a total of 111 (15.33) and they choose the based on their intuition or own decision 111 (15.33). Human resource (HR) officers and the selection board in Samar recommend the BSPM with a decision that they will probably and definitely hire graduates from the program, they will endorse it to their family and friends because SSU offers quality education, and it has free tuition, scholarship, and grants and knowing that ABM and HUMSS strands The program is feasible for the reason that it is unique in Western Samar or even in Catbalogan City which soon be offered in SSU. High demands for graduates in the government service especially in administrative staff and supervisorial functions which a management graduate is fitted to it. Supply is high and every government office is mass hiring plantilla positions to adapt support function..